McMinn's color atlas of human anatomy - Abrahams, Peter H. (Mosby, 2003)
This popular atlas maps out the structures of the human body and puts them in a clinical context. It incorporates an unrivalled collection of cadaveric, osteological, and clinical images with surface anatomy models, interpretive drawings, orientational diagrams, and diagnostic images. The 5th Edition features over 50 new dissection photos, many of which are taken from a distance to make them more recognizable in the lab setting. It also offers a more streamlined, user-friendly design, more clinical tips, and a companion CD-ROM with seven anatomical animations.